2003
DOI: 10.1289/ehp.6000
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particulate pollutants induce oxidative stress and mitochondrial damage.

Abstract: The objectives of this study were to determine whether differences in the size and composition of coarse (2.5-10 µm), fine (< 2.5 µm), and ultrafine (< 0.1 µm) particulate matter (PM) are related to their uptake in macrophages and epithelial cells and their ability to induce oxidative stress. The premise for this study is the increasing awareness that various PM components induce pulmonary inflammation through the generation of oxidative stress. Coarse, fine, and ultrafine particles (UFPs) were collected by am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
1,337
5
20

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,864 publications
(1,412 citation statements)
references
References 36 publications
31
1,337
5
20
Order By: Relevance
“…25 Only 3 patients had 11 to 12 readmissions, so we considered only 10 or fewer readmissions per patient in the analysis. Patients were considered to be at risk for recurrence from the time of first hospital encounter until the end of the observation period (December 31,2003) or their 19th birthday. Time at risk started at the first or a subsequent event and ended with each season (when time at risk begins with the next seasonal exposure) or at the next event (when time at risk begins again with the current seasonal exposure).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Only 3 patients had 11 to 12 readmissions, so we considered only 10 or fewer readmissions per patient in the analysis. Patients were considered to be at risk for recurrence from the time of first hospital encounter until the end of the observation period (December 31,2003) or their 19th birthday. Time at risk started at the first or a subsequent event and ended with each season (when time at risk begins with the next seasonal exposure) or at the next event (when time at risk begins again with the current seasonal exposure).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafine particles carry more redox-active components than larger particles, which are more spatially homogenous. 7,31,32 Based in large part on experimental evidence, it has been hypothesized that particles from vehicular exhaust, especially in the ultrafine range, can trigger oxidative stress. When antioxidant responses are then overwhelmed, airway inflammation may follow, leading to increasing asthma symptoms in susceptible children.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 99%
“…The systemic inflammatory response to particulate air pollution and its relationship to adverse coronary events in (4,6,25). Polycyclic aromatic hydrocarbons (PAH) can induce OS indirectly through its biotransformation by liver enzymes to generate redox active quinones which act as catalysts for free radical production (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAH) can induce OS indirectly through its biotransformation by liver enzymes to generate redox active quinones which act as catalysts for free radical production (5,6). In vitro reactive oxygen species (ROS) formation has been shown to be highly correlated with PAH content in air (6). The oxidation of membrane lipids, one of the primary events during oxidative cellular damage, can be assessed by measuring plasma MDA concentrations, a late-stage OS biomarker of injured cells and subcellular structures (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…To this date, however, there appears to be heterogeneity in particulate matter (PM) concentrations and PMassociated health effects between locations within an urban setting, which raises considerable uncertainties as to whether PM mass, number, size, bulk or surface chemistry are the appropriate metrics associated with PM toxicity. For example, recent studies have shown that atmospheric ultrafine particles (with physical diameter o100 nm) have the potential for eliciting adverse health effect (Oberdo¨rster and Utell, 2002;Li et al, 2003Li et al, , 2004Xia et al, 2004). Recent epidemiological studies by Peters et al (1997) have demonstrated a higher association between health effects and exposures to ultrafine particles compared to accumulation mode or coarse particles.…”
Section: Introductionmentioning
confidence: 99%